Competition policy and development in Asia - Brooks Douglas H; Evenett Simon J (Hampshire Palgrave, 2005)
This book looks at the experiences of six Asian countries in terms of developing and implementing domestic competition policy. It analyzes how the choice of development policies impacts on the state of competition in each country and how competition contr
Keywords: Asia; Economic development